2010
DOI: 10.1089/ars.2009.2842
|View full text |Cite
|
Sign up to set email alerts
|

Interplay Between Calcium and Reactive Oxygen/Nitrogen Species: An Essential Paradigm for Vascular Smooth Muscle Signaling

Abstract: Signaling cascades initiated or regulated by calcium (Ca(2+)), reactive oxygen (ROS), and nitrogen (RNS) species are essential to diverse physiological and pathological processes in vascular smooth muscle. Stimuli-induced changes in intracellular Ca(2+) regulate the activity of primary ROS and RNS, producing enzymes including NADPH oxidases (Nox) and nitric oxide synthases (NOS). At the same time, alteration in intracellular ROS and RNS production reciprocates through redox-based post-translational modificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(90 citation statements)
references
References 202 publications
6
82
0
2
Order By: Relevance
“…Intriguingly, here we show that not only age-dependent RyR1 oxidation, but also cysteine nitrosylation is reduced in MCat mice. This finding is consistent with reports that uncovered the capacity of reactive nitrogen species to regulate catalase activity in skeletal muscle (31,32). Thus, catalase overexpression may down-regulate cellular levels of nitroxide free radicals, thereby impacting cysteine nitrosylation of RyR1.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Intriguingly, here we show that not only age-dependent RyR1 oxidation, but also cysteine nitrosylation is reduced in MCat mice. This finding is consistent with reports that uncovered the capacity of reactive nitrogen species to regulate catalase activity in skeletal muscle (31,32). Thus, catalase overexpression may down-regulate cellular levels of nitroxide free radicals, thereby impacting cysteine nitrosylation of RyR1.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, it has been reported that reactive nitrogen species can substantially modulate catalase and other antioxidant enzymes in skeletal muscle (8,31,32). Thus, catalase overexpression may down-regulate cellular levels of nitroxide free radicals, thereby impacting cysteine nitrosylation of RyR1.…”
Section: Resultsmentioning
confidence: 99%
“…We will only briefly summarize the effects of ROS on TRPC channels as several reviews recently summarized the existing data [144][145][146][147]. One of the earliest reports on redox regulation of TRP channels by the Groschner group reports regulation of TRPC3 by the oxidant tBHP (tert-butylhydroperoxide).…”
Section: Redox Regulation Of Trpc Channelsmentioning
confidence: 99%
“…Although a fraction of the CAMKII pool is believed to be active, this is unlikely to account for the high basal activity observed. One explanation for this is that ROS are a potent stimulus for increased activity of CAMKII (Howe et al, 2004;Trebak et al, 2010), and the elevated levels of ROS derived from the coexpression of Nox5 may be the cause of the increased activity of WT CAMKII. Indeed, a recent study has shown that CAMKII can be directly modified by the NADPH oxidase-dependent oxidation of two methionine residues, which renders the enzyme constitutively active (Erickson et al, 2008).…”
Section: Downloaded Frommentioning
confidence: 99%